Organizational Justice, Job stress, and Cyberloafing: The Moderating Role of Islamic Workplace Spirituality - Pariyanti, Eka; Adawiyah, Wiwiek Rabiatul; Wulandari, Siti Zulaikha; Febriyanto (The Journal of Behavioral Science, 2022)
Cyberloafing is a serious problem that hinders the development of organizations today. Among academic staff, cyberloafing is detrimental to universities and disrupts the quality of teaching and learning activities. Despite abundant researches, with vast majority in non-education institutions settings, previous findings on organizational justice, job stress and cyberloafing behavior relationship are still inconclusive. This study tests Islamic workplace spirituality as a moderator in the relationship between organizational justice and job stress on cyberloafing. This research was conducted at Islamic-based universities in Lampung, Indonesia, with 178 employees as respondents. The structural equation modelling (SEM) technique was used. The results show a negative relationship between organizational justice with cyberloafing (β = -.43, p = .00) and a positive relationship between job stress and cyberloafing (β = .34, p = .00). Islamic workplace spirituality had a negative effect on cyberloafing, (β = -.15, p = .01). Islamic workplace spirituality moderates the relationship between organizational justice and cyberloafing (β = -.19, p = .02). Islamic workplace spirituality moderates the relationship between job stress and cyberloafing (β = -.04, p = .01). The research contributes to the advancement of theory in the area of employee behavior at work. The study emphasizes the significance of Islamic workplace spirituality as a means to strengthen employees’ faith, hence inducing positive behavior among employees. Employees with a greater level of spirituality in the workplace are better equipped to deal with job stress, demonstrate positive behavior, and refrain from cyberloafing.